2017
DOI: 10.2169/internalmedicine.56.7403
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implication of Plasma Hydrogen Sulfide Levels in Japanese Patients with Type 2 Diabetes

Abstract: Objective The goal of the present study was to investigate the plasma hydrogen sulfide (H2S) levels in patients with type 2 diabetes, as the plasma H2S levels in Japanese patients with type 2 diabetes remain unclear. Methods The plasma H2S levels were measured in 154 outpatients with type 2 diabetes and 66 outpatients without diabetes. All blood samples were collected in the outpatient department from 09:00 to 10:00. The patients had fasted from 21:00 the previous evening and had not consumed alcohol or caffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 29 publications
(29 reference statements)
3
52
0
1
Order By: Relevance
“…In our study, we found that the plasma H 2 S level in CKD patients was markedly lower than that in healthy controls, especially in the advanced CKD group, and this finding was confirmed by recent researches [5, 9, 17, 19]. We have also shown that the concentration of SHb, a compound consisting of methemoglobin and H 2 S (or another sulfide) [20], was significantly lower in CKD patients than that in the control.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, we found that the plasma H 2 S level in CKD patients was markedly lower than that in healthy controls, especially in the advanced CKD group, and this finding was confirmed by recent researches [5, 9, 17, 19]. We have also shown that the concentration of SHb, a compound consisting of methemoglobin and H 2 S (or another sulfide) [20], was significantly lower in CKD patients than that in the control.…”
Section: Discussionsupporting
confidence: 89%
“…Substantial evidences suggest that endogenous H 2 S presents a vital effect on signal transduction and cell protection, playing a role in nerve conduction, blood pressure control, insulin release, renal blood flow regulation, and so on. A number of diseases have been proposed to associate with decreased H 2 S level, ranging from atherosclerosis, hypertension to myocardial infarction, and diabetes mellitus [2-5]. Nevertheless, the role of H 2 S in the pathogenesis of chronic kidney disease (CKD) has not been fully investigated.…”
mentioning
confidence: 99%
“…Circulating levels of H 2 S are markedly reduced in diabetic animal models, such as diabetic rats (Jain et al, 2010;Suzuki et al, 2011), diabetic mice (Brancaleone et al, 2008), and also in diabetic patients (Jain et al, 2013;Suzuki et al, 2017). However, the mRNA level of CSE in the aortas of diabetic rats is not altered (Denizalti et al, 2011).…”
Section: H 2 S-related Endothelial Dysfunction In Diabetic Vascular Cmentioning
confidence: 99%
“…Hyperglycemia reduces the mitochondrial H 2 S pool and the plasma concentration of H 2 S, and it may deplete the buffering capacity of H 2 S in the mitochondria [94,108,109].…”
Section: Mechanism Of Damage: Cell Damaging Responses To Ros Productimentioning
confidence: 99%
“…A further target is ATP synthase in the respiratory chain: H 2 S increases cellular bioenergetics via S-sulfhydration of Complex V [122]. Since hyperglycemia reduces the H 2 S level in the cells and plasma, it will also decrease the protein S-sulfhydration and results in lower Nrf2 activity and OXPHOS efficiency [108,109].…”
Section: Mechanism Of Damage: Cell Damaging Responses To Ros Productimentioning
confidence: 99%